Evaluation of Vitamin B6 Status of Adult Saudis in Al-Qassim Region-Saudi Arabia - Al-Numair, Khalid S. (Pakistan Journal of Nutrition, 2009)
The aim of this study was to evaluate vitamin B6 status of adult Saudis in Al-Qassim region-Saudi Arabia. A sample of 239 (127 males and 112 females) healthy Saudi adults was recruited. Vitamin B6 status was evaluated by dietary intake and biochemical measurements. Results of dietary intake measurements showed that means of vitamin B6 intake and intake of vitamin B6 to protein ratio for males and females were 1.97±0.58 mg/day, 0.021±0.003 and 1.89±0.61 mg/day, 0.020±0.04, respectively. Results of biochemical measurements showed that means of plasma pyridoxal phosphate (PLP) concentration and average urinary 4-Pyridoxic Acid (4-PA) excretion for males and females were 29.6±9.6 nmol L-1 and 7.0±2.4 μmol day-1 and 31.7±10.4 nmol L-1 and 6.8±2.5 μmol day-1, respectively. The study also investigated and discussed other health indicators that are related to vitamin B6 status including Body Mass Index (BMI), plasma albumin concentration and alkaline phosphatase activity. Results of dietary intakes and biochemical measurements indicated an adequate status of vitamin B6. There were no significant differences between males and females in any of the previous measurements. This study indicated an adequate status of vitamin B6 among healthy adult Saudis in Al-Qassim region, however due to the numerous functions and the importance of the vitamin, the study suggested a further evaluation in various groups of the Saudi population in other regions of the country.